Leaf anatomy of Araucaria angustifolia (Bertol.) Kuntze (Araucariaceae) - Mastroberti,Alexandra A. (2003)
Immature and mature leaves of juvenile and adult plants of Araucaria angustifolia (Araucariaceae) were observed with the objective of updating the morphoanatomical data of the leaves of this species, which were restricted to basic descriptions in previous studies. The observations, made in optical allowed to establish anatomical differences among mature leaves of juvenile and adult plants in relation to the number of palisade parenchimal layers, the number of compartmented cells and the transfusion tissue development. Epidermis, the albuminous cells, the phloem, and the transfusion tissue descriptions are in disagreement with the data obtained data by different authors. The epidermal tissue and the hypodermis differ entirely when the plant is still juvenile, being inferred that these tissues would soon perform the protection function against mechanical damages and water loss, the vital characteristics during the first development months of young offspring.